Strategi Komunikasi Pramuwisata dalam Menjaga Eksistensi Pariwisata Bali - I Dewa Ayu Hendrawathi Putri; Ni Ketut Sri Ratmini (UHN IGB Sugriwa Denpasar, 2018)
The world of communication tourism has an important role as a medium to seek or collect information, especially in presenting the package tour (package tour). Indonesia as a nation that is building, we realize very well that the success of this nation will depend on ourselves rather than to others. Intense competition among nations (tough, fierce competition among Nations), in this case determinants that will be able to answer is the quality of human resources in various layers and various sectors both private and government. Which tourism has become the mainstay sector is expected as